The Impact of Sleep Deprivation and Weight Gain on General Health and Dietary Behavior - Talal Dakhilallah M Alanazi,; Abdullah Saad Abdullah Alshehri,; Sultan Mohammed Abdullah Almutairi,; Ali Jamaan Thamir Alharbi,; Ali Sadaqah A Ammari,; Musaad Hamed Ateeq Allah Alzibali,; Khalid Mohammed Alhusini,; Foz Salem Alanazi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Sleep deprivation and weight gain are two interrelated factors that significantly influence overall health and dietary behaviors. Chronic sleep deprivation has been linked to metabolic dysregulation, hormonal imbalances, and increased risk of obesity. Additionally, excessive weight gain contributes to numerous health complications, including cardiovascular diseases, diabetes, and cognitive impairments. This paper explores the bidirectional relationship between sleep deprivation and obesity, focusing on the underlying physiological mechanisms, behavioral patterns, and long-term health consequences. By reviewing recent literature, we aim to provide a comprehensive understanding of how inadequate sleep contributes to poor dietary choices and increased body weight, ultimately affecting public health.